Development of IOT Technology from the Angle of Patent - Yufeng Yao; Jinwen Zhu (Dianxin kexue)
The IOT technology causes high attention since it came out,and the patents about the IOT technology were increasing quickly.From the analysis of patent,readers can learn about the present status of IOT technology development.And the patent analysis is also benefit for the R＆D companies in China to prediction the trend of technology,find out the distance of technology,and choose the suitable research direction.